Silk fibroin nanofiber composite film, and preparation method and application thereof
By using a 'time-sequence separation' strategy to prepare silk fibroin nanofiber composite films, an ordered fiber network is first formed, and then the matrix phase and functional phase are filled in. This solves the problem of insufficient mechanical properties in the existing technology and achieves high density and excellent mechanical properties.
Patent Information
- Application Number
- CN202610896131.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-08-25
- Estimated Expiration
- 2046-06-22
AI Technical Summary
Existing technologies struggle to achieve ordered framework construction and controllable functional phase filling while preserving the self-assembly structure of silk fibroin nanofibers, resulting in insufficient mechanical properties of composite materials.
By employing a 'time-separation' strategy, a self-supporting film with an ordered fiber network is first prepared. Then, the matrix phase and functional phase are filled into the fiber network skeleton, and a highly dense and ordered composite film is formed through extrusion and cross-linking treatment.
The resulting composite film retains the self-assembled structure of nanofibers and has excellent mechanical properties, with a fracture strength of over 100 MPa, thus solving the problems of nanofiber aggregation and structural disorder in existing technologies.
Smart Images

Figure CN122445034B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-based nanocomposite materials technology, specifically relating to a silk fibroin nanofiber composite film, its preparation method, and its application. Background Technology
[0002] Silk fibroin is a natural structural protein derived from silkworm silk. It possesses excellent biocompatibility, biodegradability, and mechanical properties, making it suitable for various medical devices. Compared to other biomass materials such as cellulose and chitin, silk fibroin offers unique advantages in implantable applications. For instance, its degradation products are amino acids and peptides, which do not burden human metabolism. Furthermore, it can be processed in aqueous systems, avoiding the biosafety risks associated with organic solvents.
[0003] The beauty of natural silk fibers lies in their hierarchical structure. Micron-sized fibers are composed of numerous nanofibers, and each nanofiber contains highly crystalline regions. β The alternating arrangement of folded and amorphous regions gives silk fibers their superior mechanical properties, making their overall performance superior to most natural fibers and some synthetic fibers. In this multi-level structure, silk fibroin nanofibers play a crucial role: upwards, they assemble into macroscopic silk fibers through oriented alignment; downwards, their internal crystalline and amorphous regions work synergistically to endow the fibers with excellent mechanical properties.
[0004] Theoretically, if this multi-level structure could be replicated in recycled materials—that is, if nanofibers could be arranged in an orderly manner to form a continuous framework and the various levels could be tightly bound together through interfacial interactions—it would be possible to obtain mechanical properties that approach or even surpass those of natural silk. However, current technologies struggle to achieve this goal. Existing methods for preparing composite materials based on silk fibroin nanofibers can be mainly categorized as follows: (1) Nanofibers are prepared using a bottom-up reconstruction method. For example, prior art 202510732687.6 discloses a fiber-reinforced self-healing hydrogel, in which nanofibers are prepared by a bottom-up method of lithium bromide dissolution-dialysis-centrifugation-concentration-dilution-ultrasound. This method destroys the natural crystalline structure of silk, resulting in low crystallinity of the obtained nanofibers, which leads to a tensile strength of less than 30 kPa in the composite material and severely insufficient mechanical properties.
[0005] (2) Nanofibers are prepared using a top-down exfoliation method, but formed by blending. Nanofibers obtained by exfoliation (e.g., alkaline exfoliation) retain the highly crystalline structure of natural silk and theoretically possess excellent mechanical properties. However, existing technologies typically involve simple blending with polymers, with the nanofibers merely dispersed as additives in the matrix phase. The drawback of blending is that the self-assembly ability of the nanofibers is suppressed by the matrix phase, preventing the formation of an ordered continuous network, and thus failing to fully realize their structural potential as highly crystalline building blocks.
[0006] (3) Direct molding using electrospinning. For example, prior art 201310284213.7 discloses a silk fibroin nanofiber membrane, which can form a fiber network, but lacks effective adhesion between fibers, and the crystallinity of the electrospun fibers is low, with a dry breaking strength of only 8 MPa and a breaking elongation of 15%, which is orders of magnitude different from the mechanical properties of nanofibers produced by exfoliation. Although prior art 202311170804.1 discloses the use of silk fibroin solution to bond electrospun nanofibers, the breaking strength of the nanofibers is about 12 MPa.
[0007] The aforementioned blending methods and existing technologies generally suffer from the following technical problems: First, the self-assembly behavior of nanofibers is disrupted. During the blending process, the introduction of the polymer solution interferes with the interactions between nanofibers, preventing them from forming an ordered self-assembled structure and thus limiting further improvement in the material's mechanical properties. Furthermore, when nanofibers obtained through alkali exfoliation are mixed with silk fibroin solutions, the strong interaction between the two can easily lead to nanofiber aggregation, affecting structural uniformity. Second, the interfacial bonding between nanofibers and polymers is uncontrollable. In composite materials obtained through blending, nanofibers and polymers are randomly distributed, resulting in weak interfacial bonding and a tendency to generate structural defects, leading to unstable material properties.
[0008] It is evident that current technologies have failed to achieve synergistic integration of ordered framework construction and functional phase filling while retaining the natural self-assembly capability of silk fibroin nanofibers as the basic building block. Therefore, developing a method for preparing composite materials that can both preserve the self-assembly structure of nanofibers and achieve controllable functional phase filling, while also possessing excellent mechanical properties, has significant technological and application value. Summary of the Invention
[0009] To solve all or part of the above-mentioned technical problems, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a silk fibroin nanofiber composite film, comprising: S1. Provide a silk fibroin nanofiber dispersion, and form the silk fibroin nanofiber dispersion into a self-supporting film. The self-supporting film has an ordered and continuous fiber network skeleton, and the fiber network skeleton serves as a reinforcing phase. S2. Contact the self-supporting film with a solution containing a matrix phase and / or a functional phase, so that the matrix phase and / or functional phase fills the fiber network skeleton of the self-supporting film to obtain a composite precursor film. S3. The composite precursor membrane is extruded, or extruded and cross-linked, to obtain a silk fibroin nanofiber composite film.
[0010] The preparation method provided by this invention is based on a "temporal separation" strategy, that is, firstly, a self-supporting fiber network with an ordered topological structure (as a reinforcing phase) is prepared, and then the matrix phase and / or functional phase are integrated into the fiber network skeleton. The resulting silk fibroin nanofiber composite film completely retains the self-assembled structure of silk fibroin nanofibers and has good compactness and orderliness. This solves the problem that the existing co-mixing method destroys the fiber self-assembled structure, leading to nanofiber aggregation and structural disorder. The composite film prepared by the method of this invention has excellent mechanical properties.
[0011] In some embodiments, the silk fibroin nanofiber dispersion is filtered or freeze-dried to allow the silk fibroin nanofibers therein to self-assemble into the self-supporting film.
[0012] In some embodiments, the concentration of the silk fibroin nanofiber dispersion is 0.1 wt% to 20 wt%. By adjusting the concentration of the silk fibroin nanofiber dispersion, the mechanical strength of the composite film can be controlled. The nanofiber concentration affects the porosity and density of the fiber network skeleton. A low concentration results in a soft skeleton with strong plasticity, while a high concentration results in a skeleton with a higher modulus.
[0013] In some embodiments, the silk fibroin nanofibers in the silk fibroin nanofiber dispersion are obtained from silk fibers by an alkaline stripping method.
[0014] For example, the alkaline stripping method includes: placing degummed silk fibers in an alkaline solution of 0.5 g / L to 10 g / L, stirring at 2°C to 100°C for 2 hours to 720 hours, allowing the alkaline solution to selectively hydrolyze the amorphous regions to obtain a silk fibroin nanofiber dispersion; subsequently removing the alkaline solution by centrifugation and washing, and purifying by dialysis. The alkaline solution contains, for example, sodium hydroxide and / or potassium hydroxide.
[0015] In some embodiments, the silk fibroin nanofibers in the dispersion have a crystallinity of over 60%, a length of 50 nm to 200 μm, and a diameter of 10 nm to 800 nm. Using highly crystallinous silk fibroin nanofibers with a high aspect ratio allows for the construction of a high-modulus, continuous, ordered network framework in a self-supporting film. This network framework provides structural channels for the full wetting of the matrix phase. After extrusion, the interfacial contact between the matrix phase and the framework becomes tighter, thereby reducing the swelling rate of the film in phosphate buffer solution.
[0016] In some embodiments, the content of the matrix phase and / or functional phase in the solution is 0.01wt%-20wt%.
[0017] In some embodiments, the matrix phase and / or functional phase are filled into the fiber network skeleton of the self-supporting film by means of filtration and / or soaking.
[0018] In some embodiments, the matrix phase includes water-soluble polymers and / or water-insoluble polymers.
[0019] In some embodiments, the water-soluble polymer includes, but is not limited to, one or more of polyvinyl alcohol, hyaluronic acid, and silk fibroin.
[0020] In some embodiments, the water-insoluble polymer includes, but is not limited to, one or more combinations of polylactic acid-glycolic acid copolymer, polyacrylonitrile, nylon 66, thermoplastic polyurethane, polylactic acid, and polycaprolactone. The dispersant for polyacrylonitrile and thermoplastic polyurethane can be dimethylformamide, the dispersant for nylon 66 can be formic acid, and the dispersant for polylactic acid-glycolic acid copolymer, polylactic acid, and polycaprolactone can be dichloromethane, but is not limited thereto; any method that enables good dispersion of the aforementioned polymers is acceptable.
[0021] In this invention, the water-soluble and water-insoluble polymers act as a matrix. Filling the self-supporting film with these polymers effectively connects the fiber skeleton, thereby improving the film's mechanical strength without affecting the ordered and continuous fiber network skeleton formed by the self-assembly of silk fibroin nanofibers. Since the matrix phase of this invention acts similarly to a "fiber adhesive," strengthening the fiber skeleton connection and improving the film's mechanical strength, it can also be called a structural adhesive.
[0022] In some embodiments, the functional phase includes one or more of conductive materials, drug molecules, and growth factors.
[0023] In some embodiments, the conductive material includes, but is not limited to, one or a combination of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, MXene, and carbon nanotubes.
[0024] In some embodiments, the drug molecules include, but are not limited to, one or a combination of multiple anti-inflammatory drugs, antiepileptic drugs, and neurotrophic drugs.
[0025] In some embodiments, the growth factors include, but are not limited to, one or more combinations of nerve growth factor, brain-derived neurotrophic factor, and bone morphogenetic protein.
[0026] For example, the anti-inflammatory drug may be dexamethasone, minocycline hydrochloride, ibuprofen, diclofenac sodium, etc. The antiepileptic drug may be phenytoin sodium, carbamazepine, rapamycin, etc.
[0027] For water-soluble polymers and water-dispersible functional phases, they can be bound to the self-supporting membrane by filtration or immersion. For water-insoluble polymers and non-water-dispersible functional phases, they can be adsorbed and bound to the self-supporting membrane by immersion.
[0028] The method of this invention is applicable to most functional materials, including water-soluble polymers, water-insoluble polymers, conductive materials, and drug molecules, thereby expanding the application scenarios of silk fibroin nanofiber composites. In particular, it can integrate aqueously dispersed silk fibroin nanofibers with non-aqueous dispersed matrix phases and / or functional phases, solving the swelling problem of aqueous materials in a wet state.
[0029] Filling with different functional phases can endow composite films with different functions. For example, dexamethasone can be loaded to achieve anti-inflammation, nerve growth factor can be loaded to promote nerve regeneration, and PEDOT:PSS can be loaded to impart conductivity, providing a general platform for the preparation of multifunctional bioelectronic devices.
[0030] In some embodiments, multiple matrix phases and / or functional phases can be filled into the self-supporting film. For example, a solution containing multiple matrix phases and / or functional phases can be prepared first, and then the multiple matrix phases and / or functional phases can be simultaneously filled into the self-supporting film by immersion or filtration. Alternatively, different matrix phases and / or functional phases can be prepared into solutions separately, and then sequentially filled into the self-supporting film by immersion or filtration.
[0031] In some embodiments, the compression pressure is 10 kgf / cm². 2 ~1000 kgf / cm 2 The compression process takes place over a period of 2 minutes to 12 hours at a temperature of 20°C to 220°C. This compression removes excess liquid from the film and enhances the physical adhesion between fibers and between fibers and the filler.
[0032] In some embodiments, the crosslinking is chemical crosslinking and / or physical crosslinking. Further crosslinking treatment after extrusion can enhance the interfacial bonding between the fiber network and the filler, improving the stability of the composite film.
[0033] In some embodiments, the chemical crosslinking includes: placing the precursor composite film obtained by the extrusion into a vapor crosslinking vapor containing a crosslinking agent.
[0034] In some embodiments, the crosslinking agent includes one or a combination of two of glutaraldehyde and genipin.
[0035] In some embodiments, the temperature for vapor crosslinking is 20-100°C.
[0036] In some embodiments, the vapor crosslinking time is 6 hours to 48 hours.
[0037] In some embodiments, the physical crosslinking includes: steam annealing the precursor composite film obtained by the extrusion in water vapor, methanol vapor, ethanol vapor or diphenylethanol vapor.
[0038] In some embodiments, the temperature of the steam annealing is 4°C-100°C.
[0039] In some embodiments, the steam annealing time is 12 hours to 48 hours.
[0040] In some embodiments, the preparation method further includes repeating steps S2-S3 multiple times.
[0041] In some embodiments, after extrusion and optional crosslinking treatment, a drying step may also be performed.
[0042] A second aspect of the present invention provides a silk fibroin nanofiber composite film, which is prepared by any of the preparation methods described in the present invention.
[0043] In some embodiments, the silk fibroin nanofiber composite film contains 16.3 to 98.2 wt% silk fibroin nanofibers and 1.8 to 83.7 wt% matrix phase and / or functional phase.
[0044] In some embodiments, the tensile strength of the silk fibroin nanofiber composite film is above 100 MPa.
[0045] In some embodiments, the swelling rate of the silk fibroin nanofiber composite film in phosphate buffer is less than 20%.
[0046] In some embodiments, the silk fibroin nanofiber composite film exhibits birefringence under a cross-polarizer.
[0047] The silk fibroin nanofibers obtained by the alkaline exfoliation method of this invention have high crystallinity, and their mechanical properties are superior to those of nanofibers obtained by the "bottom-up" reconstruction method in the prior art. Meanwhile, because the composite film prepared based on the "temporal separation" strategy retains the ordered fiber network skeleton, it can provide an efficient stress transfer network, thus enabling the composite film to exhibit excellent mechanical properties. In some embodiments, the breaking strength can reach over 100 MPa, significantly higher than that of composite materials prepared by blending and electrospinning methods.
[0048] A third aspect of the present invention provides a multilayer silk fibroin nanofiber composite material, comprising a plurality of said silk fibroin nanofiber composite films stacked in the thickness direction, wherein the adjacent silk fibroin nanofiber composite films are rotated at an angle of 0° to 180°.
[0049] A fourth aspect of the present invention provides a method for preparing the aforementioned multilayer silk fibroin nanofiber composite material, comprising: Silk fibroin nanofiber composite films are prepared by any of the technical solutions described above. Multiple silk fibroin nanofiber composite films are stacked in the thickness direction, and the adjacent silk fibroin nanofiber composite films are rotated at an angle of 0° to 180° to obtain an intermediate material. The intermediate material is extruded and cross-linked to obtain a multilayer silk fibroin nanofiber composite material.
[0050] In some embodiments, the preparation method further includes: soaking the intermediate material in a solution containing a matrix phase and / or a functional phase, followed by extrusion and drying. Further selection of the matrix phase and functional phase has been detailed in the first aspect of this invention and will not be repeated here. The matrix phase and functional phase used in the preparation method of the multilayer silk fibroin nanofiber composite material can be the same as or different from the matrix phase and functional phase used in the preparation of a single-layer film.
[0051] In some embodiments, the rotation angle can be any angle or a range between any two angles from 0°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 45°, 60°, 75°, and 90°, such as 0° to 90°, more preferably 15° to 35°. By adjusting the rotation angle, the tensile strength of the multilayer silk fibroin nanofiber composite film can be controlled.
[0052] The number of layers can be flexibly adjusted according to actual needs, such as greater than 1 and less than or equal to 100 layers.
[0053] The fifth aspect of the present invention provides the application of the aforementioned silk fibroin nanofiber composite film and the aforementioned multilayer silk fibroin nanofiber composite material in the preparation of implantable medical devices or biosensors.
[0054] In some embodiments, the implantable medical device includes a substrate material for an implantable neural electrode, a tissue-engineered scaffold, a drug delivery carrier, or a bone repair material.
[0055] The single-layer composite film and multi-layer composite material prepared by this invention have high mechanical strength, low swelling rate, good biocompatibility and functional integrability, making them particularly suitable as flexible substrate materials for implantable neural electrodes. They can also be widely used in biomedical fields such as tissue engineering scaffolds, drug delivery carriers, biosensors and bone repair.
[0056] Compared with the prior art, the present invention has at least some or all of the following beneficial effects: The preparation method provided by the present invention is based on the "temporal separation" strategy, that is, firstly, a self-supporting fiber network with an ordered topological structure is prepared as a reinforcing phase, and then the matrix phase and / or functional phase are integrated into the fiber network skeleton. The resulting silk fibroin nanofiber composite film completely retains the self-assembly structure of silk fibroin nanofibers and has good density and order. The composite film prepared by the present invention has high density and high strength characteristics and excellent mechanical properties. It solves the problem that the composite film prepared by the blending method in the prior art destroys the fiber self-assembly structure, resulting in nanofiber aggregation and structural disorder. Attached Figure Description
[0057] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0058] Figure 1 This is a flowchart of the preparation process for Example 1; Figure 2 This is a SEM image of the silk fibroin nanofiber composite film prepared in Example 2e. Figure 3 This is a flowchart of the preparation process in Example 4; Figure 4 This is a SEM image of the self-supporting film prepared using a 5wt% concentration of silk fibroin nanofiber dispersion in Example 4. Figure 5 The stress-strain curve of the silk fibroin nanofiber composite film prepared in Example 4 using a 5 wt% concentration of silk fibroin nanofiber dispersion and a 15 wt% concentration of silk fibroin aqueous solution is shown. Figure 6 This is an orthogonally polarized photograph of the composite film prepared in Example 4 using a 2.5 wt% concentration of silk fibroin nanofiber dispersion and a 5 wt% silk fibroin aqueous solution. Figure 7 These are macroscopic photographs and surface microstructure images of the silk fibroin nanofiber composite film prepared in Example 5 using 2.5wt% silk fibroin nanofiber dispersion and 7.5wt% polylactic acid solution. Figure 8 The mechanical property test diagrams are for the films prepared in Example 1a, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Figure 9 The mechanical properties of the thin film prepared in Comparative Example 4 are shown in the test diagram. Figure 10 This is a photograph of the fiber aggregation state during the drying process of direct mixing and drying of silk fibroin nanofiber dispersion and silk fibroin solution in Comparative Example 5. Detailed Implementation
[0059] The invention will be more fully understood through the following detailed description of its embodiments. The detailed embodiments disclosed herein are merely illustrative, and the invention may be embodied in various forms. Therefore, the specific functional details disclosed herein should not be construed as limiting, but rather as the basis for the claims.
[0060] In addition, unless otherwise specified, all raw materials used in the following embodiments can be purchased from the market or other sources, and all production and testing equipment used are known in the art, as are the testing methods used.
[0061] Example 1a This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method. Figure 1 This is a flowchart of the preparation process in this embodiment, which specifically includes the following steps: (1) Preparation of silk fibroin nanofiber dispersion: 10g of silk (Hongtong Silk Technology Co., Ltd., white raw silk, grade 5A) was cut into pieces and then boiled in 1L of 0.05% (mass-volume ratio) sodium carbonate solution for 30 minutes. After removing the silk, it was washed 5 times with deionized water and dried in an oven at 45℃ until constant weight to obtain degummed silk. A 5g / L potassium hydroxide solution was prepared, and the degummed silk was added to the potassium hydroxide solution at a bath ratio of 2.5g:1L. The solution was magnetically stirred until the fibers were dispersed into nanofibers. The length of the nanofibers obtained by exfoliation was 50 nm~50 μm, the diameter was in the range of 10~300 nm, and the crystallinity was 60.7%. The nanofibers obtained by alkaline exfoliation were centrifuged and dialyzed. The dialyzed fibers were dispersed by ultrasonication to prepare a 2.5wt% silk fibroin nanofiber dispersion.
[0062] (2) Preparation of self-supporting membrane: A nanofiltration membrane with a size of 5 cm and a pore size of 0.45 μm was selected, and the silk fibroin nanofiber dispersion was filtered by a vacuum filtration device to obtain a self-supporting membrane with an ordered topological structure.
[0063] (3) Matrix phase coating: Prepare a 10wt% polyvinyl alcohol solution (model PVA1799). Take 2ml of polyvinyl alcohol solution and add it evenly to the self-supporting film obtained in step (2). Disperse the polymer solution into the self-supporting film by filtration. Then use filter paper to remove the excess polyvinyl alcohol solution on the surface to obtain the composite precursor film.
[0064] (4) Extrusion and chemical crosslinking: The composite precursor film obtained in step (3) is transferred between two sheets of cleanroom paper and then placed on an extruder with a pressure of 200 kgf / cm. 2 The film was extruded for 60 minutes at a temperature of 120°C. Then, the film was transferred to glutaraldehyde vapor (at a temperature of 80°C) for vapor crosslinking for 6 hours. After removal and drying, silk fibroin nanofiber composite film was obtained.
[0065] Examples 1b-1e Examples 1b-1e are basically the same as Example 1a, except that the concentration of the silk fibroin nanofiber dispersion in step (1) is varied as shown in Table 1. The rest are the same as in Example 1a, and will not be repeated here.
[0066] The mass percentage of silk fibroin nanofibers and polyvinyl alcohol in the silk fibroin nanofiber composite film was determined. The determination steps were as follows: the self-supporting film from step (2) of Example 1a was placed on an extruder, and the pressure was set to 200 kgf / cm. 2The film was extruded for 60 minutes at a temperature of 120°C. After the temperature dropped to room temperature, it was weighed and recorded as W1. The film after hot pressing and before vapor crosslinking in step (4) of Example 1a was weighed and recorded as W2. The percentage increase in mass before and after was calculated to determine the ratio of the two in the composite film. The test results are summarized in Table 1.
[0067] Table 1. Concentration of silk fibroin nanofiber dispersion and mass percentage of silk fibroin nanofibers and polyvinyl alcohol in the films used in Examples 1a-1e
[0068] Examples 2a-2e Examples 2a-2e are basically the same as Example 1a, except that the concentration of the polyvinyl alcohol solution used in step (3) is varied as shown in Table 2. The rest are the same as in Example 1a, and will not be repeated here.
[0069] Table 2. Polyvinyl alcohol solution concentration and mass percentage of silk fibroin nanofibers and polyvinyl alcohol in the films used in Examples 2a-2e
[0070] Examples 3a-3c Examples 3a-3c are basically the same as Example 1a, except that the crosslinking time in step (4) is changed according to Table 3. The rest are the same as in Example 1a, and will not be repeated here.
[0071] Table 3 Crosslinking times in Examples 3a-3c
[0072] Figure 2 This is a SEM image of the silk fibroin nanofiber composite film prepared in Example 2e.
[0073] Comparing Examples 1a-1e and 2a-2e above, it was found that the mechanical properties of the composite film are related to the concentration of the nanofiber dispersion, the concentration of the matrix phase solution, and the crosslinking time. The mechanical properties of the composite film were measured using a tensile tester at a tensile speed of 5 mm / min. The tests showed that the mechanical properties of the composite film increased with increasing polyvinyl alcohol concentration. When the concentration of silk fibroin nanofibers was 5 wt% and the concentration of polyvinyl alcohol was 5 wt%, the tensile strength of the composite film was 170.4 MPa, and the wet strength was 120.1 MPa. The tensile strength of the composite film decreased with decreasing nanofiber dispersion concentration. Increasing the steam crosslinking treatment time from 6 hours to 48 hours improved the tensile strength of the composite film by 23.7%. Therefore, considering the excellent mechanical properties of the composite film, the preferred concentration of the silk fibroin nanofiber dispersion is 2.5 wt% to 5.0 wt%, the preferred concentration of the matrix phase in the matrix phase solution is 1 wt% to 5 wt%, and the preferred crosslinking treatment time is 12 hours to 36 hours.
[0074] Example 4 This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method. Figure 3 This is a flowchart of the preparation process in this embodiment, which specifically includes the following steps: (1) Preparation of silk fibroin nanofiber dispersion: Prepare a 5 g / L potassium hydroxide solution, mix degummed silk with potassium hydroxide solution at a bath ratio of 2.5 g: 1 L, stir magnetically until the fiber is dispersed into micro-nanofibers, then centrifuge and dialyze, and disperse the dialyzed fiber by ultrasonication to prepare silk fibroin nanofiber dispersions with concentrations of 2.5 wt% and 5 wt%.
[0075] (2) The above silk fibroin nanofiber dispersion was freeze-formed and then freeze-dried using a freeze dryer to obtain a self-supporting film.
[0076] (3) Degummed silk was added to a 9.3 mol / L lithium bromide solution at a bath ratio of 1 g: 4 mL, heated at 60 °C for 2 hours, and then the mixture was sealed in a dialysis bag and dialyzed in pure water for 3 days to remove excess salt ions. The solution was then centrifuged to obtain a silk fibroin aqueous solution. Silk fibroin aqueous solutions with concentrations of 5 wt%, 7.5 wt%, 10 wt%, 12.5 wt%, and 15 wt% were prepared according to this method. The self-supporting membranes prepared above were immersed in the above-mentioned silk fibroin aqueous solutions of different concentrations for 2 hours respectively. After removal, excess silk fibroin on the surface was absorbed with filter paper to obtain a composite precursor membrane.
[0077] (4) Transfer the composite precursor film obtained above between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 50 kgf / cm². 2 The extrusion temperature was 180℃ and the extrusion time was 10 minutes. The extruded film was then transferred to methanol vapor (temperature 80℃) for vapor annealing for 12 hours, and then dried to obtain a silk fibroin nanofiber composite film.
[0078] The porosity of the material before and after hot pressing in this embodiment was determined using the liquid drainage method. The test method is as follows: A certain weight of film was completely immersed in n-butanol solution for 5 minutes. After removal, the n-butanol on the surface of the film was absorbed with filter paper, and the weight difference before and after was recorded. M Record the volume change of the n-butanol solution before and after. V The porosity is calculated using the formula ( ε ): ε (%) = M / V × 100 in, ρ The density of n-butanol ( ρ = 0.81 g / cm 3 ).
[0079] Calculations show that the porosities of the self-supporting films obtained by freeze-drying 2.5 wt% and 5 wt% silk fibroin nanofiber dispersions in step (2) of this embodiment are 83.2±4.2% and 67.7±3.8%, respectively. After directly extruding this self-supporting film (without silk fibroin coating) in step (4), the porosities decreased to 3.4±1.1% and 3.1±1.3%, respectively.
[0080] If the film is soaked in a 5 wt% silk fibroin solution for 2 hours before extrusion, and then subjected to extrusion and physical cross-linking treatment in step (4), the porosity of the resulting film is further reduced to 0.65±0.24% and 0.23±0.12%. This is because, during the soaking process, silk fibroin molecules penetrate and fill the pores of the fiber network, forming a denser composite structure after extrusion and physical cross-linking. When the concentration of silk fibroin is increased to 15 wt%, the porosity is as low as 0.11±0.09%. It should be noted that when the concentration of silk fibroin exceeds 7.5 wt%, the difference in film porosity is small, and there is no significant statistical difference between different concentrations. This is because the high concentration of silk fibroin solution has almost completely filled the pores of the fiber network, and the porosity is close to the lower limit of the intrinsic density of the material. Further increasing the concentration will have a saturated effect on reducing porosity.
[0081] Figure 4This is a SEM image of the self-supporting film prepared using a 5 wt% concentration of silk fibroin nanofiber dispersion in Example 4, as shown. Figure 4 As shown, the self-supporting film prepared by freeze drying has good formability and orientation.
[0082] Figure 5 The stress-strain curve of the silk fibroin nanofiber composite film prepared in Example 4 using a 5 wt% concentration of silk fibroin nanofiber dispersion and a 15 wt% concentration of silk fibroin aqueous solution is shown. Its tensile strength is 298.5 MPa, and its tensile strain is 5.5%, significantly better than the composite films prepared by blending (tensile strength approximately 50 MPa) and electrospinning (tensile strength approximately 8 MPa). Furthermore, the tensile strength gradually increases with increasing concentration of the silk fibroin aqueous solution, because silk fibroin can fully fill the pores of the fiber network, enhancing the interfacial bonding and load transfer efficiency between fibers. The composite film prepared using a 2.5 wt% concentration of silk fibroin nanofiber dispersion and a 5 wt% concentration of silk fibroin aqueous solution still achieves a mechanical strength of 138.1 MPa. The concentration of the silk fibroin aqueous solution can be adjusted according to different application scenarios.
[0083] Figure 6 This is an orthogonally polarized photograph of the composite film prepared in Example 4 using a 2.5 wt% silk fibroin nanofiber dispersion and a 5 wt% silk fibroin aqueous solution. Figure 6 As shown, the composite film exhibits a distinct color under polarized light, indicating birefringence. This suggests that an ordered fiber network structure has formed within the composite film. This characteristic allows the composite film to serve as a substrate with structural anisotropy without the need for an external orientation device. It is expected to simulate the natural structure of ordered human tissues such as nerves, muscles, and ligaments, providing material support for tissue repair or tissue engineering.
[0084] Example 5 This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method, specifically including the following steps: (1) Preparation of silk fibroin nanofiber dispersion: Prepare a 10 g / L sodium hydroxide solution, mix degummed silk with sodium hydroxide solution at a bath ratio of 10 g: 1 L, stir magnetically until the fiber is dispersed into micro-nanofibers, then centrifuge and dialyze, and disperse the dialyzed fiber by ultrasonication to obtain silk fibroin nanofiber dispersions with concentrations of 1 wt%, 2.5 wt%, 5 wt%, 7.5 wt%, and 10 wt%.
[0085] (2) The above silk fibroin nanofiber dispersion was freeze-formed and then dried by a freeze dryer to obtain a self-supporting film.
[0086] (3) Dissolve polylactic acid (molecular weight number average 100,000) in dichloromethane to prepare polylactic acid solutions with concentrations of 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, and 15wt%. Immerse the above self-supporting membrane in the polylactic acid solution for 2 hours, and then remove it and use filter paper to absorb the excess polylactic acid solution on the surface to obtain the composite precursor membrane.
[0087] (4) Transfer the composite precursor film obtained above between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 50 kgf / cm². 2 The extrusion temperature was 40℃ and the extrusion time was 12 hours to obtain a silk fibroin nanofiber composite film.
[0088] Figure 7 These are macroscopic photographs and surface microstructure images of the silk fibroin nanofiber composite film prepared in Example 5 using a 2.5 wt% silk fibroin nanofiber dispersion and a 7.5 wt% polylactic acid solution. Figure 7 As shown, the composite film exhibits good formability. Furthermore, with increasing concentration of the silk fibroin nanofiber dispersion, the structure of the self-supporting film becomes denser, enhancing its resistance to deformation. The mechanical properties of the composite film obtained after polylactic acid solution coating and extrusion treatment are further increased because polylactic acid can embed itself into the nanofiber skeleton and act as a connector, similar to silk fibroin in Example 4. When the concentration of the silk fibroin nanofiber dispersion is 7.5 wt% and the polylactic acid solution is 7.5 wt%, the tensile strength of the resulting composite film is 123.2 MPa. When the concentration of the silk fibroin nanofiber dispersion increases to 10 wt%, while keeping the amount of polylactic acid constant, the tensile strength of the composite film increases by 46.9 MPa.
[0089] The present invention also tested the swelling ratio of the self-supporting film and composite film prepared in Example 5. The test method is as follows: A certain mass of film (denoted as M1) was weighed and added to 10 mM PBS (phosphate buffer, pH 7.4) at a concentration of 1 mg / mL. The film was placed in a 37°C oven and removed after a set time. The surface buffer was absorbed with filter paper, and the weight of the film at this time was recorded (denoted as M2). Then, the percentage increase in film weight was calculated and recorded as the swelling ratio of the film. When the weight no longer changes, this value is the maximum swelling ratio of the film. The swelling ratios of the films after testing and statistics are shown in Table 1 below.
[0090] The self-supporting film in Table 4 was prepared using a 2.5 wt% silk fibroin nanofiber dispersion, and the silk fibroin nanofiber composite film was prepared using a 2.5 wt% silk fibroin nanofiber dispersion and polylactic acid solutions of different concentrations.
[0091] Table 4 Maximum swelling ratio of self-supporting films and composite films
[0092] As shown in Table 4, the maximum swelling ratio of the composite film is significantly lower than that of the self-supporting film. This is because polylactic acid fills the pores of the fiber network, reducing the water-holding space. Furthermore, as the concentration of the polylactic acid solution gradually increases, the maximum swelling ratio gradually decreases. This is because higher concentrations of polylactic acid form a denser filling layer, further restricting the penetration of water molecules.
[0093] Example 6a The difference between Example 6a and Example 4 is that the concentration of the silk fibroin nanofiber dispersion is 5 wt%, the concentration of the silk fibroin solution is 7.5 wt%, the steam annealing uses diphenylethanol, the annealing temperature gradient is set to 20℃, 40℃, 60℃, 80℃, and 100℃, and the treatment time is 12 hours. The remaining steps are the same as in Example 4 and will not be repeated here.
[0094] The film prepared in Example 6 was characterized according to the method for testing swelling ratio described in Example 5. The tests revealed that the steam annealing time affected the swelling ratio of the composite film. As the annealing temperature increased from 20°C to 100°C, the swelling ratio decreased from 62% to 16.4%, improving the film's stability in phosphate buffer. This is because increasing the temperature enhances the ability of diphenylethanol vapor to induce the movement of silk fibroin molecular chains, promoting... β - The formation and crystallization of the folded structure make the interface between the silk fibroin nanofiber network skeleton and the silk fibroin matrix more compact, reducing the free volume and thus inhibiting the penetration of water molecules and the swelling of the film.
[0095] Examples 6b-6f Examples 6b-6f are basically the same as Example 6a, except that the crosslinking agent genipin (dissolved in anhydrous ethanol at a concentration of 5 mg / mL) is used for chemical crosslinking, and the crosslinking time and temperature are varied as shown in Table 5. The rest are the same as in Example 6a, and will not be described again here.
[0096] Table 5 Crosslinking times in Examples 6b-6f
[0097] The principle behind genipin treatment of silk fibroin is that genipin reacts with the primary amino groups of lysine residues on the silk fibroin molecular chain, forming covalent bonds that connect adjacent molecular chains, thereby constructing a stable three-dimensional network structure. When the material's color changes from colorless to light blue, it indicates that the cross-linking reaction has occurred. As the treatment time increases, the film color gradually deepens, indicating that the degree of cross-linking is continuously increasing. When the color change is no longer obvious, it indicates that the cross-linking reaction has reached saturation.
[0098] Example 7 The only difference between Example 7 and Example 4 is that the concentration of the silk fibroin nanofiber dispersion used in Example 7 is 5 wt%; the coating solution is a hyaluronic acid solution, and hyaluronic acid solutions of different concentrations (0.5 wt%, 1 wt%, 2 wt%, and 3 wt%) were prepared to prepare the silk fibroin nanofiber composite film. The rest of the procedures are the same as in Example 4 and will not be repeated here.
[0099] Tests revealed that when the concentration of the silk fibroin nanofiber dispersion was 5 wt% and the concentration of hyaluronic acid was 3 wt%, the tensile strength of the silk fibroin nanofiber composite film was 188.5 MPa, and the tensile strain was 7.3%, exhibiting excellent mechanical properties. The tensile strength of the composite film prepared with 3 wt% hyaluronic acid was 1.9 times that of the composite film prepared with 1 wt% hyaluronic acid, and the tensile strain was 1.5 times that of the composite film prepared with 3 wt% hyaluronic acid.
[0100] Example 8 The only difference between Example 8 and Example 5 is that the concentration of the silk fibroin nanofiber dispersion used in Example 8 is 1 wt%; the coating solution is polylactic acid-glycolic acid copolymer (PLGA), and different concentrations of PLGA solutions (2.5 wt%, 5 wt%, 10 wt%, and 15 wt%) are prepared to prepare silk fibroin nanofiber composite films. The rest of the procedures are the same as in Example 5 and will not be repeated here.
[0101] When the concentration of the silk fibroin nanofiber dispersion was 1 wt% and the concentration of PLGA was 5 wt%, the swelling rate of the prepared silk fibroin nanofiber composite film in PBS was 6.3%.
[0102] Example 9 The only difference between Example 9 and Example 5 is that the concentration of the silk fibroin nanofiber dispersion used in Example 9 is 7.5 wt%; the coating solution is a polyacrylonitrile (PAN) solution, and polyacrylonitrile solutions of different concentrations of 2.5 wt%, 5 wt%, 10 wt%, and 15 wt% were prepared to prepare silk fibroin nanofiber composite films.
[0103] When the concentration of the silk fibroin nanofiber dispersion was 7.5 wt% and the concentration of the PAN solution was 2.5 wt%, the swelling rate of the prepared silk fibroin nanofiber composite film in PBS was 9.7%.
[0104] Example 10 This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method, specifically including the following steps: (1) Preparation of silk fibroin nanofiber dispersion: Prepare a 10 g / L sodium hydroxide solution, mix degummed silk with sodium hydroxide solution at a bath ratio of 10 g: 1 L, stir magnetically until the fiber is dispersed into micro-nanofibers, then centrifuge and dialyze, and disperse the dialyzed fiber by ultrasonication to obtain a 5 wt% concentration of silk fibroin nanofiber dispersion.
[0105] (2) The above silk fibroin nanofiber dispersion was freeze-formed and then freeze-dried using a freeze dryer to obtain a self-supporting film.
[0106] (3) Nylon 66 was dissolved in formic acid to prepare formic acid solutions with Nylon 66 concentrations of 2.5 wt%, 5 wt%, 7.5 wt%, 10 wt%, and 15 wt%. The self-supporting membrane was immersed in the formic acid solution of Nylon 66. After ten minutes, the Nylon 66 in the pores of the membrane was gently squeezed out with filter paper and dried. Then, the membrane was immersed in a 2 wt% MXene aqueous solution for 30 minutes. After immersion, the solution on the surface was absorbed with filter paper and dried at 60°C. Next, the membrane was immersed in a 2 wt% anhydrous ethanol solution of carbon nanotubes for 30 minutes. The drying-immersion steps were repeated 1-5 times to obtain the composite precursor membrane.
[0107] (4) Transfer the composite precursor film obtained above between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 50 kgf / cm². 2 The extrusion temperature was 40℃ and the extrusion time was 6 hours to obtain a silk fibroin nanofiber composite film.
[0108] When the concentration of the silk fibroin nanofiber dispersion is 5 wt% and the concentration of the nylon 66 formic acid solution is 2.5 wt%, the tensile strength of the silk fibroin nanofiber composite film is 124.5 MPa and the strain is 6.8%. Furthermore, as the concentration of the nylon 66 formic acid solution increases, the mechanical properties of the composite film also improve; when the concentration of nylon 66 increases to 10 wt%, the strength of the composite film is 210.6 MPa.
[0109] Example 11 This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method, specifically including the following steps: (1) Preparation of silk fibroin nanofiber dispersion: Prepare a 5 g / L potassium hydroxide solution, mix degummed silk with potassium hydroxide solution at a bath ratio of 2.5 g: 1 L, stir magnetically until the fiber is dispersed into micro-nanofibers, then centrifuge and dialyze, and disperse the dialyzed fiber by ultrasonication to obtain a 5 wt% concentration of silk fibroin nanofiber dispersion.
[0110] (2) The above silk fibroin nanofiber dispersion was freeze-formed and then freeze-dried using a freeze dryer to obtain a self-supporting film.
[0111] (3) The above self-supporting film was immersed in a 3 wt% plastic polyurethane dispersion for 1 hour. After immersion, the thermoplastic polyurethane in the pores of the film was gently squeezed out with filter paper and dried. Then, the film was immersed in a PEDOT:PSS solution (Heraeste pH 1000) for 30 minutes. After immersion, the solution on the surface was absorbed with filter paper and dried at 80°C. Then, the film was transferred to ethanol and immersed for 10 minutes. After drying, it was immersed in PEDOT:PSS again. The PEDOT:PSS immersion-drying-ethanol treatment steps were repeated 1-5 times to obtain the composite precursor film.
[0112] (4) Transfer the composite precursor film obtained above between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 50 kgf / cm². 2 The extrusion temperature was 220℃ and the extrusion time was 2 minutes to obtain a silk fibroin nanofiber composite film.
[0113] Measurements showed that after three immersions in PEDOT:PSS, the conductivity of the silk fibroin nanofiber composite film reached 170 S / cm. The conductivity of the composite film can be controlled by optimizing the number of immersions in PEDOT:PSS, making it suitable as a substrate material for neural electrodes.
[0114] Example 12a This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method, specifically including the following steps: (1) Preparation of silk fibroin nanofiber dispersion: Prepare a 5 g / L potassium hydroxide solution, mix degummed silk with potassium hydroxide solution at a bath ratio of 2.5 g: 1 L, stir magnetically until the fiber is dispersed into micro-nanofibers, then centrifuge and dialyze, and disperse the dialyzed fiber by ultrasonication to obtain a 5 wt% concentration of silk fibroin nanofiber dispersion.
[0115] (2) The above silk fibroin nanofiber dispersion was freeze-formed and then freeze-dried using a freeze dryer to obtain a self-supporting film.
[0116] (3) Dissolve dexamethasone in ethanol to prepare a drug solution of 0.1 mg / mL; immerse the above self-supporting membrane in the drug solution for 30 minutes, then remove it and wait for the solvent to evaporate, and then immerse it in silk fibroin solutions of different concentrations (5 wt%, 7.5 wt%, 10 wt%, 12.5 wt%, 15 wt%, 17.5 wt%, 20 wt%) to obtain a composite precursor membrane.
[0117] (4) Transfer the composite precursor film obtained above between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 50 kgf / cm². 2 The extrusion temperature was 180℃ and the extrusion time was 10 minutes. The extruded film was then transferred to methanol vapor (temperature 80℃) for vapor annealing for 12 hours, and then dried to obtain a silk fibroin nanofiber composite film.
[0118] In this embodiment, a drug-loaded self-supporting film is immersed in silk fibroin solutions of varying concentrations. The silk fibroin physically coats the nanofibers and the drug surface. After annealing with methanol vapor, the film is then subjected to controlled temperature adjustments. β - The release rate of drugs can be regulated by the fold content and structural density. Increasing the concentration of silk fibroin and self-supporting film can delay the release rate of drugs.
[0119] Examples 12b-12d Examples 12b-12d are basically the same as Example 12a, except that the drugs used and the solvents used to prepare the drug solutions are changed according to Table 6.
[0120] Table 6. Drugs used in Examples 12a-12d and solvents used to prepare drug solutions
[0121] Example 13a This embodiment provides a silk fibroin nanofiber composite film based on a time-sequential separation strategy and its preparation method, specifically including the following steps: (1) Prepare a silk fibroin nanofiber dispersion with a concentration of 2.5 wt%. Select a nanofiltration membrane with a size of 5 cm and a pore size of 0.45 μm. Use a vacuum filtration device to filter the silk fibroin nanofiber dispersion to obtain a self-supporting film with an ordered topological structure.
[0122] (2) Dissolve minocycline hydrochloride in a 2 wt% polyvinyl alcohol aqueous solution to ensure a drug concentration of 0.1 mg / mL. Disperse fibroblast growth factor (FGF-1) in a phosphate buffer solution, and then disperse it in a 3 wt% silk fibroin solution (FGF-1 final concentration is 1 μg / mL). Immerse the above self-supporting membrane first in a minocycline hydrochloride / polyvinyl alcohol solution, and then in an FGF-1 / silk fibroin solution to obtain a composite precursor membrane.
[0123] (3) Transfer the prepared composite precursor film between two sheets of cleanroom paper, and then place it on an extruder with a pressure of 10 kgf / cm². 2 100kgf / cm 2 300kgf / cm2 500 kgf / cm 2 1000 kgf / cm 2 The extrusion temperature was 20℃ (room temperature), and the extrusion time was 12 hours. The extruded film was then placed in an environment at 4℃, where water slowly evaporated and contacted the film for 48 hours, resulting in a silk fibroin nanofiber composite film. The principle is that water molecules penetrate into the amorphous regions of the silk fibroin and form hydrogen bonds with some groups (such as -OH and -NH2) on the silk fibroin molecular chains. This process increases the mobility of the molecular chains in the amorphous regions, inducing an increase in the proportion of crystalline regions in the silk fibroin structure, thus achieving cross-linking.
[0124] Comparison of composite films prepared under different extrusion pressures revealed that the drug release rate slowed down and the release cycle increased with increasing extrusion pressure. This is because higher extrusion pressure makes the fiber network skeleton denser and enhances the interfacial bonding between the matrix phase and the fibers, thereby increasing the path resistance of drug diffusion and delaying the release rate.
[0125] Examples 13b-13c Examples 13b and 13c are basically the same as Example 13a, except that the type of drug packaging in step (2) is changed according to Table 7, the drug is replaced with diclofenac sodium or phenytoin sodium, and the growth factor is replaced with brain-derived neurotrophic factor (BDNF) or bone morphogenetic protein (BMP-2). The rest are the same as in Example 13a, and will not be repeated here.
[0126] Table 7. Drug types and formulations used in Examples 13a-13c
[0127] Example 14 This embodiment provides a multilayer silk fibroin nanofiber composite material and its preparation method, specifically including: Following the method in Example 4, a monolayer silk fibroin nanofiber composite film was prepared using a 1.5 wt% silk fibroin nanofiber dispersion and a 5 wt% silk fibroin solution. Forty monolayer silk fibroin nanofiber composite films were taken and divided into four groups. Each group was then immersed in the 5 wt% silk fibroin solution. After removal, excess silk fibroin on the surface was absorbed using filter paper. The films were then stacked at different rotation angles. Group 1: Ten single-layer silk fibroin nanofiber composite films are stacked with an interlayer rotation angle of 0°.
[0128] Group 2: Ten single-layer silk fibroin nanofiber composite films were stacked with an interlayer rotation angle of 5° clockwise.
[0129] Group 3: Ten single-layer silk fibroin nanofiber composite films were stacked with an interlayer rotation angle of 15° clockwise.
[0130] Group 4: Ten single-layer silk fibroin nanofiber composite films were stacked with an interlayer rotation angle of 35° clockwise.
[0131] After stacking, the multilayered films are extruded at a pressure of 150 kgf / cm². 2 The extrusion temperature was 160℃, and the extrusion time was 30 minutes. Finally, the extruded film was transferred to methanol vapor (temperature 80℃) for vapor annealing for 24 hours, and then dried to obtain a multilayer silk fibroin nanofiber composite film.
[0132] Tensile properties were tested on the obtained multilayer silk fibroin nanofiber composites. The results showed that the fracture strengths of the multilayer silk fibroin nanofiber composites prepared by the stacking methods in groups 1, 2, 3, and 4 were 217.8 MPa, 370.2 MPa, 573.6 MPa, and 401.5 MPa, respectively. Each composite exhibited strong birefringence, and its mechanical properties could be further controlled by changing the rotation angle. Considering the need for excellent mechanical properties, the preferred interlayer rotation angle range is 15°–35°.
[0133] Comparative Example 1 The only difference between Comparative Example 1 and Example 1a is that Comparative Example 1 directly mixed 2.5 wt% silk fibroin nanofiber dispersion with 10 wt% polyvinyl alcohol solution to ensure that the mass ratio of silk fibroin nanofiber to polyvinyl alcohol is 1:1, and then air-dried at room temperature to obtain a film.
[0134] Comparative Example 2 The only difference between Comparative Example 2 and Example 1a is that Comparative Example 2 does not use polyvinyl alcohol solution to impregnate the self-supporting film. The rest of the procedures are the same as in Example 1a and will not be repeated here.
[0135] Comparative Example 3 The only difference between Comparative Example 3 and Example 1a is that the 2.5 wt% silk fibroin nanofiber dispersion in Comparative Example 3 was replaced with a 2.5 wt% silk fibroin solution. The rest of the procedures were the same as in Example 1a and will not be repeated here.
[0136] Figure 8The figures show the mechanical properties of the films prepared in Examples 1a, 1, 2, and 3. Comparing Examples 1a and 1-3, the composite film prepared in Example 1a exhibits a tensile strength of 146.3 MPa, which is 2.5 times that of Comparative Example 1, 5.8 times that of Comparative Example 2, and 1.5 times that of Comparative Example 3, respectively. The mechanical properties of the composite film prepared using the method of this invention are significantly improved compared to Comparative Examples 1-2. This is because the method of this invention constructs a continuous composite structure of an ordered fiber network and a polyvinyl alcohol matrix phase, achieving a synergistic enhancement effect between the load-bearing capacity of the fiber skeleton and the stress transfer of the matrix phase. In contrast, Comparative Example 1 has disordered fiber dispersion and weak interfacial bonding, while Comparative Example 2 lacks matrix phase filling, both failing to form an effective stress transfer network. Furthermore, the mechanical properties of the composite film prepared by the method of Example 1a are significantly higher than those of Comparative Example 3. This is because Comparative Example 3 lacks the skeletal support of silk fibroin nanofibers, leading to a decrease in its mechanical properties, thus demonstrating the reinforcing advantage of silk fibroin nanofibers as a skeleton.
[0137] Comparative Example 4 The only difference between Comparative Example 4 and Example 4 is that in step (1) of Comparative Example 4, the 5 wt% silk fibroin nanofiber dispersion was replaced with a 5 wt% silk fibroin solution (the preparation method is the same as in Example 4; the chemical reagents destroyed the crystallization structure of the degummed silk, so the crystallinity was less than 20%). In step (2) of Comparative Example 4, the freeze-dried silk fibroin film was immersed in an ethanol / water solution (the volume ratio of ethanol to water was 4:1) for 20 minutes, and then dried. The purpose of this step is to ensure that the freeze-dried silk fibroin film has a stable structure during the immersion process in step (4). In step (4) of Comparative Example 4, a 15 wt% silk fibroin solution was selected to immerse the silk fibroin film. The rest were carried out in the same manner as in Example 4, and will not be repeated here.
[0138] Figure 9 The graphs show the mechanical properties of the thin film prepared in Comparative Example 4. (Comparison) Figure 5 , Figure 9 It is evident that the composite film prepared in Example 4 exhibits significantly higher mechanical properties than the film in Comparative Example 4, demonstrating that the silk fibroin nanofiber framework is crucial for enhancing the material's mechanical properties. This invention achieves a composite film with high mechanical strength by arranging nanofibers in an orderly manner to form a continuous framework and utilizing the strong adhesive effect between the matrix and the framework. Combined with the inherent biocompatibility of silk fibroin, this composite film shows broad application prospects in the fields of implantable medical devices or biosensors.
[0139] Comparative Example 5 The only difference between Comparative Example 5 and Example 4 is that Comparative Example 5 directly mixes 5 wt% silk fibroin nanofiber dispersion and 5 wt% silk fibroin solution in equal volume ratio, and then directly dries them to prepare composite materials.
[0140] Figure 10 The image shown is a photograph of the fiber aggregation state during the drying process of the direct blending and drying of silk fibroin nanofiber dispersion and silk fibroin solution in Comparative Example 5. Figure 10 As shown, after direct blending, silk fibroin nanofibers readily aggregate and flocculate in the silk fibroin solution, making it difficult to form a uniform film. This indicates that the incompatibility of silk fibroin nanofibers with other matrix phases affects the self-assembly characteristics of the nanofibers themselves. However, the sequential separation strategy of "self-assembling to form a framework first, then filling" in this invention can completely preserve the self-assembled structure of silk fibroin nanofibers.
[0141] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0142] All aspects, embodiments, features, and examples of this invention should be considered illustrative and used to explain and illustrate the invention, but not to limit it. The scope of the invention is defined only by the claims.
[0143] Although the invention has been described with reference to the above embodiments, those skilled in the art will understand that various other changes, omissions, and / or additions can be made without departing from the spirit and scope of the invention, and that substantially equivalents can be substituted for elements in the described embodiments. Therefore, the invention is not intended to be limited to the specific embodiments disclosed, but rather to encompass all embodiments falling within the scope defined by the claims.
Claims
1. A method for preparing a silk fibroin nanofiber composite film, characterized in that, include: S1. A silk fibroin nanofiber dispersion is provided, and the silk fibroin nanofiber dispersion is filtered or freeze-dried to allow the silk fibroin nanofibers therein to self-assemble into a self-supporting film. The self-supporting film has an ordered and continuous fiber network skeleton, which serves as a reinforcing phase. The silk fibroin nanofibers in the silk fibroin nanofiber dispersion have a crystallinity of more than 60%, a length of 50 nm to 200 μm, and a diameter of 10 nm to 800 nm. S2. The self-supporting film is brought into contact with a solution containing a matrix phase and / or a functional phase. The matrix phase and / or functional phase are then incorporated into the fiber network framework of the self-supporting film using filtration and / or immersion methods to obtain a composite precursor membrane. The content of the matrix phase and / or functional phase in the solution is 0.01 wt%-20%. wt%; the matrix phase comprises water-soluble polymers and / or water-insoluble polymers, wherein the water-soluble polymers include one or more of polyvinyl alcohol, hyaluronic acid, and silk fibroin, and the water-insoluble polymers include one or more of polylactic acid-glycolic acid copolymer, polyacrylonitrile, nylon 66, thermoplastic polyurethane, polylactic acid, and polycaprolactone; the functional phase comprises one or more of conductive materials, drug molecules, and growth factors, wherein the conductive materials include one or more of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, MXene, and carbon nanotubes, the drug molecules include one or more of anti-inflammatory drugs, antiepileptic drugs, and neurotrophic drugs, and the growth factors include one or more of nerve growth factor, brain-derived neurotrophic factor, and bone morphogenetic protein; S3. The composite precursor membrane is extruded, or extruded and cross-linked, to obtain a silk fibroin nanofiber composite film.
2. The method for preparing the silk fibroin nanofiber composite film according to claim 1, characterized in that, The concentration of the silk fibroin nanofiber dispersion is 0.1 wt% to 20 wt%.
3. The method for preparing the silk fibroin nanofiber composite film according to claim 1, characterized in that, The silk fibroin nanofiber dispersion contains silk fibroin nanofibers obtained from silk fibers via an alkaline stripping method.
4. The method for preparing the silk fibroin nanofiber composite film according to claim 1, characterized in that, The extrusion pressure is 10 kgf / cm². 2 ~1000 kgf / cm 2 The time ranges from 2 minutes to 12 hours, and the temperature ranges from 20℃ to 220℃.
5. The method for preparing the silk fibroin nanofiber composite film according to claim 1, characterized in that, The crosslinking is chemical crosslinking and / or physical crosslinking.
6. The method for preparing the silk fibroin nanofiber composite film according to claim 1, characterized in that, Repeat steps S2-S3 multiple times.
7. The method for preparing the silk fibroin nanofiber composite film according to claim 5, characterized in that, The chemical crosslinking includes: placing the film obtained by the extrusion into a vapor crosslinking vapor containing a crosslinking agent.
8. The method for preparing the silk fibroin nanofiber composite film according to claim 5, characterized in that, The physical crosslinking includes: steam annealing the film obtained by the extrusion in water vapor, methanol vapor, ethanol vapor or diphenylethanol vapor.
9. A silk fibroin nanofiber composite film, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The silk fibroin nanofiber composite film according to claim 9, characterized in that, The silk fibroin nanofiber composite film has a tensile strength of 100 MPa or higher, and / or the swelling rate of the silk fibroin nanofiber composite film in phosphate buffer is less than 20%, and / or the silk fibroin nanofiber composite film exhibits birefringence under a cross polarizer.
11. The silk fibroin nanofiber composite film according to claim 9, characterized in that, The silk fibroin nanofiber composite film contains 16.3 to 98.2 wt% silk fibroin nanofibers and 1.8 to 83.7 wt% matrix phase and / or functional phase.
12. A multilayer silk fibroin nanofiber composite material, characterized in that, The invention includes multiple silk fibroin nanofiber composite films according to any one of claims 9-11 stacked in the thickness direction, wherein the adjacent silk fibroin nanofiber composite films are rotated at an angle of 0° to 180°.
13. The method for preparing the multilayer silk fibroin nanofiber composite material according to claim 12, characterized in that, include: Silk fibroin nanofiber composite films were prepared by the preparation method according to any one of claims 1-8; Multiple silk fibroin nanofiber composite films are stacked in the thickness direction, and the adjacent silk fibroin nanofiber composite films are rotated at an angle of 0° to 180° to obtain an intermediate material. The intermediate material is extruded and cross-linked to obtain a multilayer silk fibroin nanofiber composite material.
14. The use of the silk fibroin nanofiber composite film according to any one of claims 9-11 and the multilayer silk fibroin nanofiber composite material according to claim 12 in the preparation of implantable medical devices or biosensors.
15. The application according to claim 14, characterized in that, The implantable medical device includes a substrate material for an implantable neural electrode, a tissue engineering scaffold, a drug delivery carrier, or a bone repair material.
Citation Information
Patent Citations
Silk fibroin nanofiber membrane and preparation method thereof
CN103341209B
Flexible strong and tough waterborne thin films, methods of making and applications thereof
CN117188155B
Preparation method of fiber-reinforced self-repairing hydrogel mediated sequential drug release scaffold for promoting vascularized osteochondral regeneration
CN120571077A
Preparation method of silk fibroin / graphene composite nano fiber support material
CN106913910A
Bionic nano fiber material as well as preparation method thereof and application thereof
CN111793899A